Substance P aggravates ligature-induced periodontitis in mice - Siddiqui, Yasir Dilshad; Nie, Xuguang; Wang, Sheng; Abbasi, Yasaman; Park, Lauren; Fan, Xiaoxuan; Thumbigere-Math, Vivek; Chung, Man-Kyo (Frontiers in Immunology, 2023)
Periodontitis is one of the most common oral diseases in humans, affecting over 40% of adult Americans. Pain-sensing nerves, or nociceptors, sense local environmental changes and often contain neuropeptides. Recent studies have suggested that nociceptors magnify host response and regulate bone loss in the periodontium. A subset of nociceptors projected to periodontium contains neuropeptides, such as calcitonin gene-related peptide (CGRP) or substance P (SP). However, the specific roles of neuropeptides from nociceptive neural terminals in periodontitis remain to be determined. In this study, we investigated the roles of neuropeptides on host responses and bone loss in ligature-induced periodontitis. Deletion of tachykinin precursor 1 (Tac1), a gene that encodes SP, or treatment of gingiva with SP antagonist significantly reduced bone loss in ligature-induced periodontitis, whereas deletion of calcitonin related polypeptide alpha (Calca), a gene that encodes CGRP, showed a marginal role on bone loss. Ligature-induced recruitment of leukocytes, including neutrophils, and increase in cytokines leading to bone loss in periodontium was significantly less in Tac1 KO mice. Furthermore, intra-gingival injection of SP, but not neurokinin A, induced a vigorous inflammatory response and osteoclast activation in alveolar bone and facilitated bone loss in ligature-induced periodontitis. Altogether, our data suggest that SP plays significant roles in regulating host responses and bone resorption in ligature-induced periodontitis.